PENGARUH PENGAWASAN TERHADAP SEMANGAT KERJA PEGAWAI PADA KANTOR KELURAHAN AIR PUTIH KECAMATAN SAMARINDA ULU KOTA SAMARINDA - Jurlena, Eida (PREDIKSI, 2012)
The purpose of this study was to determine whether the monitoring effect on employee morale. To get the data the authors counducted a study on the Village Office White Water District Samarinda ulu samarinda city.The results showed that the control effect on employee morale at the Village Office White Water District Samarinda Ulu Samarinda City.It can be proven that the result of the analysis of data abtained rs count greater than the price table is 0.770>0.456 at 95% confidence level for N = 14